Gambaran Karakteristik Akseptor KB Suntik 3 Bulan dengan Amenorea Sekunder di BPM Bidan “S” Curug Tangerang 2017 - Putri Handayani Setyaningsih (Edu Masda Journal, 2019)
Based on the survey results of January - April 2017 aksetor number of injections 3 months in Midwives BPM "S" Curug Tangerang as many as 425 people. From the data obtained acceptor injections three months did not experience any side effects that 23%, and who experience side effects from injections of 3 months as many as 77%, consisting of amenorrhea were 75 %, which experienced a weight gain as many as 19.5%, and those with spoting 5.5%. The purpose of this research is to describe the characteristics of 3-month injectable acceptors with secondary amenorrhea by age, parity, KB long, long experienced menstrual disorders. The methodology in this paper uses descriptive method types. The place is BPM Midwives "S" Curug Tangerang. The study design used is Cross Sectional. With a population of 315 people. Large samples taken 76 respondents and retrieval techniques samplenya with "Non-Probability Sampling" method used was "accidental sampling". Data collected by the secondary data through medical records. Analysis of the data used univariate analysis. The results obtained are based on age, 76 more than half sebayak 56 people aged 20-35 (73.7%). Based on parity, more than half of the 76 acceptors grande multipara many as 48 people (63.1%). Based on the old family planning with a long of 76 half berKB ≥ 24 months as many as 41 people. Based on long experience disruption of 76 is less than half as many menstrual disorders 6-10 years as many as 31 people.